DIABETES MELLITUS: RECENT ADVANCEMENT IN PPAR AGONISTS AS THERAPEUTIC AGENTS - GOPAL L. KHATIK, (International Journal of Pharma and Bio Sciences, 2015)
Diabetes mellitus is known as metabolic disorder related to glucose intolerance which is characterized by hyperglycemia. Diabetes mellitus can be treated by insulin and oral hypoglycemic agents. Most of known oral hypoglycemic are peroxisome proliferator-activated receptors (PPAR) agonist. There are three different subtypes of PPARs are identified and they are involved in glucose metabolism. A balanced PPARs agonist is required to avoid consequences related to over activation of one of the receptor subtypes. PPAR agonist has a good influence on activation of PPAR due to their chirality, therefore this review discusses the advancement and role of chirality on PPAR activation by PPAR agonists.